ANALISIS BERPIKIR KREATIF SISWA DALAM PEMECAHAN MASALAH PERSAMAAN KUADRAT - Loiulro, Rolina; Mataheru, Wilmintjie; Ngilawajan, Darma A (Atom : Jurnal Riset Mahasiswa, 2023)
This study aims to describe the creative thinking of class IX students of Kusu-Kusu Christian Middle School, Sereh Ambon, in solving quadratic equation problems. The type of research used is descriptive qualitative, carried out at the Kusu-kusu Christian Middle School Sereh Ambon in the odd semester of the 2020/2021 academic year. This study's data sources were grade IX students with a total of 6 subjects, namely two subjects with high, medium, and low abilities. Three subjects were interviewed from the creative thinking test results, namely, 1 with high, medium, and low abilities. Two instruments are used in this study: the main instrument, the researcher, acts as a data collector: a companion instrument, creative thinking test sheets and interview guidelines. Data collection techniques are in the form of tests given to subjects who have studied the quadratic equation material, interviews conducted after the subjects have completed the test questions, and documentation, namely photos and videos, by following the steps of the data collection procedure. Data analysis techniques were carried out using data reduction, namely removing interview snippet data that were not by the research flow, presenting data in the form of narrative texts, and conclusions or verification, namely drawing conclusions based on test and interview results, for objectivity and validity. Data is used with credibility (degree of trust), which involves triangulation of sources. The results showed that high-ability subjects could solve three questions properly and correctly, which met all indicators of creative thinking in solving problems. Moderately capable subjects could only solve two questions and only met several indicators of creative thinking, and low-ability subjects could not complete questions correctly and adequately